An Impact Assesment of Boko Haram Insurgency on Commercial Activities in Mubi Town - Sajo, Salama (IJRDO - Journal of Social Science and Humanities Research, 2018)
The deadly insurgent group, Boko Haram had in the last seven years (from 2009 -2015) gradually and systematically made the entire northeastern Nigeria vulnerable in terms of security. Although Plateau State and the Federal Capital Territory, Abuja, got their own share of the sect’s attacks, the worst affected is the northeast. Mubi as one of the big commercial towns in the northeast, no doubt, would be one of the admired targets of the insurgents. The sporadic insurgent attacks by the Boko Haram in Mubi started in the year 2012. By the year 2014, their activities had heightened which eventually led to the capture of the commercial town. This paper reveals the impact of the Boko Haram insurgency on commercial activities in Mubi metropolis which include among others, loss of lives including business operators, destruction of shops and other corporate buildings, loss of money and valuable items and decline of some business partners who felt the town is not safe for business. In fact, some business operators did not return to Mubi since the insurgents overran the town. At the end of the study, recommendations were made on how to revitalize commercial activities in Mubi.